General Motors: a failure of corporate philosophy - Schoemaker, Paul J. H. (Henry Stewart Talks, 2018)
This case study describes the failure of GM in the late 1960s to foresee changes in the automotive industry. They held several assumptions that, although already beginning to be incorrect, were not questioned by the company in their strategic planning.
Archived at 2024/02/11